(untitled) (Africa Development, 2021)
Contents China in West Africa’s Regional Development and Security Plans Emmanuel Akyeampong................................1 Knowledge is Power and Power Affects Knowledge: The Challenges for Research Collaboration in and with Africa Henning Melber......................................21 Le financement de l’éducation dans les collectives locales, quels défis ? Marie Elisabeth Dembele............................43 Uganda’s Vision 2040 and Human Needs Promotion Moses Senkosi Balyejjusa ......................... 61 Exploring Thought Leadership, Thought Liberation and Critical Consciousness for Africa’s Development Vusi Gumede......................................91 The Role of Older Persons in Uganda: Assessing Socio-demographic Determinants of Older Persons’ Value Abel Nzabona & James Ntozi....................113 Igilango Geesi in the Public Sphere: Soyinka’s Intervention in the Nigerian Political Discourse Dipo Irele............................... 137 Political Uncertainty and its Impact on Social Service Delivery in Uganda Moses Khisa............................. 159